Fenologia e propagação de Amburana cearensis (Arr. Cam.) A.C. Smith - Santos, Severino do Ramo Nascimento dos (2014)
Plants are subject to external and internal variables that may affect the plant physiological ecology. The precipitation, temperature, photoperiod, intensity of solar radiation, hormones and others operate in the processes of growth and development of plants. Understanding the factors that affect the biology of the species is essential for plantations or forest management driving. The objective of this research was to study the phenology and the propagation of Amburana cearensis. The research was conducted at the farm dam, municipality of Soledade-PB and Seed Analysis Laboratory and Tissue Culture of the Federal University of Paraiba. For the phenology held the selection of thirty individuals using the track sampling, followed by georeferencing. The observations occurred at fortnightly intervals, recording phenophases: senescence, budding, flower bud, anthesis and fruit. Also evaluated were different temperatures and substrates for driving germination and vigor of seeds. To assess the emergence and early seedling growth, the following substrates were used: 1) Soil area of seed collection; 2) Basaplant®; 3) Vermiculite; 4) Humus earthworm; 5) Solo collecting area of the seeds + Basaplant® (1: 1); 6) Solo collecting area of the seeds + vermiculite (1: 1); 7) Solo collecting area of the seeds + earthworm humus (1: 1). Seeding was performed manually, using two seeds in each container rigid plastic and polyethylene core. In micropropagation evaluated the influence of different culture media, explants and regulating hormones. According to the results the budding starts even in the dry season, and intensifies with the rains; senescence is intensified with the formation of fruit; the reproductive period (flower bud, anthesis and fruit) is over. For A. cearensis seed germination test can be used paper substrate germitest® at constant temperatures of 25 and 30 ºC, and alternating 20-30 ºC with satisfactory results. In general, the substrates applied in mixture (soil + basaplant®, soil, vermiculite and soil + earthworm humus) associated with plastic provide the emergency, the vigor and growth of seedlings of A. cearensis; the seedlings of A. cearensis have rapid growth up to 30 days. The medium B5 provides the best conditions for germination and early seedling growth of A. cearensis; for germination and early growth of seedlings of A. cearensis not use of sucrose is required in the culture medium; the explant cotyledon node A. cearensis seedlings demonstrates better organogenic competence in the multiplication xx step; the presence of plant growth regulators BAP and ANA has little influence on the growth of shoots in explants A. cearensis; the concentrations of the plant growth regulator AIB favored the emission of root explants A. cearensis; the acclimation of seedlings of A. cearensis the conditions used was low.